'It's Not Dark Yet, but It's Getting There': Listening for the End Times in the Contemporary American Novel. Issue 1 (31st March 2016) - Masterson, John
Abstract : This article argues that contemporary imaginings of the end times are dominated, and sometimes skewed, by visual culture. By focusing on three post-9/11 American novels, Freedom, A Visit from the Goon Squad and Stone Arabia, I suggest their peculiar preoccupation with music offers a compelling supplement to the proliferation of eschatological discourses in the historical present. Franzen, Egan and Spiotta attend to musicians battling with their own versions of end times, invariably splicing personal and political apocalypses, as well as questions of ethics and aesthetics as they do so. Drawing on the work of cultural commentators such as Greil Marcus and Simon Reynolds, as well as thinkers and theorists including Jean Baudrillard, Zygmunt Bauman, Frank Kermode and Edward Said, the article argues that a greater sensitivity to the distinctive contribution of music and musicians to these debates can enliven them in particular ways. By placing concerns with the production, consumption and circulation of music at the heart of their respective texts, Franzen, Egan and Spiotta suggest how and why some of the more hegemonic tendencies in end times discourses might be set to a different rhythm. In so doing, they invite us to listen to them anew.